Evaluación de eficiencia de las medidas de control, implementadas a los riesgos físicos y químicos del área operativa de abastecimiento, armado y soldadura en la empresa Sedemi - Gómez Yugsi, Henry Javier (2022)
The purpose of this study is to evaluate the physical and chemical risks in the operational areas of supply, assembly and welding of the company SEDEMI dedicated to the manufacture, construction and assembly of metal structures, a field research is proposed that leads to the identification and quantitative evaluation of pollutants resulting from the use of machinery such as welding machines, thermal cutters, oxyfuel equipment, plasma, welding towers, bending machines, folding machines, shot blasting and grinder use, These values obtained in measurement have been compared with the TLV (Threshold Limit Value) allowing to determine those pollutants that are affecting the health of the worker in an acute or chronic way, expanding the perspective of the true condition of the workplaces and how effective and successful are the control measures that are being implemented in the company, Once the attenuation and exposure index have been determined, it can be concluded that within the physical risks, noise is 93% controlled as is thermal stress at 100%, unlike vibration and lighting, which reflect deficiency in the control with 62.5% and 25% respectively, warning of possible illnesses that may occur in the worker if they are not corrected, As with the chemical risks where the concentration indexes of pollutants in the environment are well above the acceptable ones, with 83% "UNDETERMINATE" and only 17% as "ACCEPTABLE", due to the saturation of gases, vapors, metal fumes and lack of ventilation, characterizing this risk with greater criticality by the effects they cause in the exposed person, concluding that control measures should be focused on the source and the environment but not on the person.